RANCANGAN SOP PUBLIKASI ARTIKEL JURNAL VOK@SINDO UNIT BPJ FAKULTAS VOKASI UNIVERSITAS BRAWIJAYA DALAM BENTUK INFOGRAFIS - Khoirunnisa, Pavita (Politeknik Ubaya, 2024)
Publication of Vok@sindo Journal Articles is a systematic activity starting from sending articles according to the Vok@sindo journal template until the article is published on OJS. This study aims to design a Standard Operating Procedure (SOP) for the Publication of Vok@sindo Journal Articles BPJ unit at the Faculty of Vocational Studies, Universitas Brawijaya in the form of infographics. The research method used in this research is a qualitative method with data collection techniques carried out by interview, observation and documentation. The result of this Final Project is the need for SOP in the form of infographics to make it more attractive and can be used for standing banners and as information media, it is necessary to design Standard Operating Procedures (SOP) for the Publication of Vok@sindo Journal Articles in the form of infographics. This is the essence of your SOP. Here you describe what needs to be done, the order of the tasks, and methodology your employees need to follow. You can list the different steps and if the process is more complex, include sub-steps to describe all activities in detail.Also, include supplementary diagrams, images, or illustrations when appropriate. Imagery can sometimes be a more effective way of explaining how to get things done. Copyright © 2024 by Authors, Published by Jurnal Bisnis Terapan. This work is licensed under a Creative Commons. Attribution-ShareAlike 4.0 International License